Upaya Mengatasi Hambatan dalam Implementasi Kurikulum Merdeka di SDN Mawo Dana - Dangga, Noviani Peka; Daga, Agustinus Tanggu; Lende, Petrus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the challenges faced and the efforts made by SD Negeri Mawo Dana in implementing the Merdeka Curriculum. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that the implementation of the Merdeka Curriculum at SD Negeri Mawo Dana still encounters several obstacles, including limited teacher understanding of the curriculum structure and principles, inadequate educational facilities, challenges in conducting assessments and Pancasila Student Profile (P5) projects, and difficulties in developing appropriate teaching modules and assessment instruments. To address these issues, the school has undertaken several initiatives such as conducting training through Teacher Working Groups (KKG), using simple and contextual learning media, utilizing the Merdeka Mengajar Platform (PMM) as a reference and enrichment source, and providing teacher mentoring in developing learning tools. This study recommends continuous support from school leaders, improvement of learning facilities, and sustained assistance from the local education office to optimize and sustain the implementation of the Merdeka Curriculum